Variations of cosmic rays in the period 2016-2019 according to observations of the ENU experimental complex - Морзабаев, А.К.; Тулеков , Е.; Махмутов , В.; Ерхов , В.; Филиппов , М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
This article presents brief characteristics of the CARPET installation of the scientific cosmo-physical experimental complex created at the L. N. Gumilyov Eurasian National University (ENU) and experimental data obtained in the period 2016-2019. Separate results of the analysis of registered variations in cosmic ray fluxes and conditions in the earth’s magnetosphere and interplanetary medium are presented. The authors present a method for determining the barometric coefficient for correcting the obtained data. The article considers the dynamics of measurements of experimental data obtained on other neutron monitors coincide well with the series of measurement data carried out using the CARPET detector. The purpose of continuous monitoring and research at the ENU scientific cosmo-physical experimental complex is to study variations in the fluxes of secondary cosmic rays. This work shows that the experimental data obtained using the CARPET detector makes it possible to study the properties of cosmic ray variations at different time intervals under the conditions of processes occurring on the Sun, in the interplanetary medium, and on the surface of the surface atmospheric layer. A wide time spectrum of variations of secondary cosmic rays – short-term (Forbush effect, solar effects, etc.), long-term-is studied. Quantitative characteristics of the radiation fields and the possibility of interpreting the data obtained are obtained. A number of data on charged particle fluxes obtained in the course of this work can be used to solve problems related to the modulation and influence of cosmic rays on magnetospheric and atmospheric processes. The data obtained using the CARPET detector and the results of experimental work allow for long-term research and will complement the global data Bank of secondary cosmic ray fluxes.